The advertisement call of Proceratophrys branti Brandão, Caramaschi, Vaz-Silva & Campos, 2013 (Amphibia, Anura, Odontophrynidae) - de Andrade, Sheila Pereira; Rocha, Cezar Filho; Vaz-Silva, Wilian (Zootaxa, 2018)
Proceratophrys Miranda-Ribeiro, 1920 currently comprises 40 species (Frost 2017) of which 15 are allocated into the Proceratophrys cristiceps species group (sensu Brandão et al. 2013). The species in this group are characterized by the absence of postocular swellings and, except for P. concavitympanum, are found in seasonally open habitats in Brazilian Cerrado and Caatinga morphoclimatic domains (Giaretta et al. 2000; Ávila et al. 2012; Teixeira Jr. et al. 2012; Brandão et al. 2013). Information on advertisement calls is available for 11 species of the group (Eterovick & Sazima 1998; Nunes & Juncá 2006; Brasileiro et al. 2008; Santana et al. 2010; Ávila et al. 2012; Martins & Giaretta 2011; 2012; 2013; Ferreira et al. 2016). Proceratophrys branti Brandão, Carmaschi, Vaz-Silva & Campos, 2013 has been recently described and allocated in the P. cristiceps species group. The species occurs in open areas in the north-central portion of the Brazilian Cerrado, in the states of Goiás, Minas Gerais and Tocantins (Brandão et al. 2013). Herein we describe for the first time its advertisement call, based on recordings made in an area of Cerrado biome in the state of Tocantins.